Telas da memória: Representação da sociedade platina nas pinturas de Pedro Weingärtner e Juan Manuel Blanes (século XIX e XX) - Fochesatto, Cyanna Missaglia de (Universidade do Vale do Rio dos Sinos, 2019)
This research aims to investigate the pictorial representations of the social types of Brazil and Uruguay, through paintings by Pedro Weingärtner (1853-1929) and Juan Manuel Blanes (1830-1901), between the 19th and 20th centuries. It seeks to understand the formation of identities and social imaginaries through the use made of the paintings of these two artists. This thesis is part of a qualitative research within the perspective of the practices and representations under the theoretical references of the New Cultural History. We investigate vestiges and symbolisms that were part of the development of Brazilian and Uruguayan society. To contribute to the development of the thesis authors such as Michael Baxandall (2006), Roger Chartier (1996) and Erin Panofsky (1991) were used. The Brazilian painter, Pedro Weingärtner, spent part of his life between the New and Old World, portrayed broadly the social types that inhabited the southern region of the country, such as the gaucho and the European immigrant, as well as a large production of portraits of the elite social and political life. The Uruguayan painter, Juan Manuel Blanes, represented the characters of Uruguay, such as the gaucho, the military and the social and political elite, consecrated as the "painter of the homeland" when representing paintings commissioned by historical themes. In this sense, this research proposes to study the use made of the production of these two painters, as well as the memory that the paintings express, aiming the understanding and the function of these paintings for the construction of an identity, an imaginary and a representation - both Brazilian and Uruguayan society.
Keywords: Representação; Pintura; Pedro Weingärtner; Juan Manuel Blanes; Imaginários; Representation; Painting; Pedro Weingärtner; Juan Manuel Blanes; Imaginary; ACCNPQ::Ciências Humanas::História